Investigating English Teachers’ Communicative Strategies and Learning Feedback in Constructing Classroom Discourses of EFL Learners - Sofiyah Cahyani; Selma Al-Qasri; Wafika Ofara (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2023)
Communication refers to the process of exchanging information between individuals, namely the sender and the receiver, with the aim of achieving mutual understanding. In an educational setting, communication strategies serve as a blueprint for how information is exchanged. In particular, the use of effective communication strategies by teachers is critical in constructing classroom discourse in English as a Foreign Language (EFL) classrooms. Such strategies and feedback from teachers are indispensable for students to enhance their abilities and performance in the classroom. Classroom discourse plays a vital role in the learning process, and teachers should consider it during the teaching and learning process. Consequently, this study aims to investigate the communication strategies utilized by teachers in constructing classroom discourse in EFL classrooms, as well as the types of feedback they employ to maintain interaction with their students during teaching and learning processes. To collect the required data, the researcher conducted qualitative descriptive research, using interview notes, note-taking, and observation. The participants were male and female English teachers who taught at different grade levels, including tenth and eleventh grades. The researcher interviewed English teachers regarding their communication strategies and the types of feedback they use during teaching and learning processes. The findings revealed that teachers employed five types of communication strategies, including literal translation, code-switching, nonverbal signals, fillers and hesitation-gambits, self and other-repetition, and appeals for help. The results indicate that the use of such strategies is effective in improving students' performance and ability in class. Additionally, the feedback that teachers use during teaching and learning processes can be categorized into two types, namely oral and visual feedback, which can be given on an individual or group basis.